Infrared Thermography Using Thermal Eddy Current Excitation for Non-Destructive Testing of Multi-Layer Epoxy-Carbon Composites - Waldemar ŚWIDERSKI1 (Termografia w podczerwieni ze stymulacją cieplną prądami wirowymi w badaniach nieniszczących wielowarstwowych kompozytów epoksydowo-węglowych, 2017)
The eddy current thermography method is a new technique for the non-destructive detection of cracks in materials based on the conduction of an electric current. It is a combination of eddy current testing and thermography. Eddy currents are used to heat the tested sample, while the defect detection is based on changes in the temperature field profile on its surface, as recorded by a thermographic camera. The article discusses numerical modelling methods supporting the thermographic non-destructive testing of composites and presents example results of the tests.
Keywords: Termografia w badaniach nieniszczących